(untitled) (Fiep Bulletin - online, 2014)
This article aims to discuss the importance of initial training apart from the technical and biological issues and has focused on the formation of a critical teacher, and it has the supervised curricular as the core content of the discussion. It starts with the premise that the Physical Education in higher school requires many areas that enable the vision of all human movement, however, seems to occur in a natural excessive preoccupation with biological and technical content and a lack of theoretical teaching to discuss critically the various spheres of activity of the Physical Education teacher.